Regular Islamic prayers have different corpus callosum: a shape analysis study - Baykara, Sema; Baykara, Murat; Atmaca, Murad (Springer, 2023)
BackgroundReligious practices and experiences are thought to involve a variety of thoughts and behaviors, and various studies hypothesize the relationship between religion and changes in the brain. The aim of this study was to evaluate the corpus callosum (CC) of prayers by statistical shape analysis (SSA) and compare it with healthy ones who did not.MethodsThe study group consisted of 13 healthy people who pray regularly and the control group consisted of 14 healthy people who did not pray. Participants were scanned with a 1.5 T scanner and a high-resolution structural image of the entire brain was obtained with sagittal 3D spiral fast spin echo. In mid-sagittal images of each individual, the CC was marked using landmarks. The mean of 'Procrustes' points was calculated and shape deformations were evaluated using thin plate spline analysis.ResultsThere was no significant difference between the CC area of prayers and controls. Maximum CC deformation was observed in the body and rostrum region markings during prayers. There was no significant difference in the other parameters of the individuals who performed regular prayers compared to the controls.ConclusionsCorpus callosum analysis with SSA revealed differences between prayers and healthies. The study findings highlighted the abnormal distribution of white matter in the CC and the variable subregional nature of CC in prayers. The study findings showed that shape analysis could be a useful technique to show variations in the corpus callosum using MRI images.
Keywords: Religion and science; Islam; Corpus callosum; Image processing; Computer-assisted; Magnetic resonance imaging